Clinico epidemiological study of thermal burns in a tertiary care hospital - G., Ravikumar; P., Shanmugapriya; G. R., Sugapradha; R., Senthamilselvi (International Surgery Journal, 2019)
Background: Substantial number of people suffers from burn injuries every year in India that make the patients endure disease, surgeries and years of rehabilitation. The higher mortality and prolonged morbidity results in heavy social, economic and clinical burden to the nation. The objective was to study and analyse the socio-demographic profile of burn patients in addition to evaluate the causes, manner and clinical course of burn patients along with its outcome. Methods: This was a registry based retrospective study on 114 burns patients, admitted in a Tertiary Care Hospital in South India from January 2018 to June 2018. Data were collected and assimilated comprehensively. Results: The age group of patients ranged from 13-70 years, the mean age being 29 years. The overall male, female to transgender ratio was 0.57:1:0.01. Most of the patients were married (66.66%). The TBSA involvement in burns ranged from 10% to 100% and the mean TBSA was found to be 11.4±2.95. A higher TBSA involvement is associated with an increased risk of mortality and this association between TBSA and mortality was found to be statistically significant (p<0.05). Mortality ratio in this study was 51.75% and septic shock (58%) was the most common cause of death followed by hypovolemic shock (42%). Conclusions: Burns are one of the leading causes of preventable morbidity and mortality, provided the prevention strategies address the hazards of specific burn injuries, awareness education for vulnerable population and targeted first aid training.